Bundled Database Subscriptions: Challenges, Opportunities, and Assessment. Issue 1 (2nd January 2016) - Tabacaru, Simona; Pickett, Carmelita; Stephens, Jane; Ugaz, Ana; Ramirez, Diana; Xiao, Daniel; Harrell, Jeanne; Reddy, Deva E.
ABSTRACT: This case study describes the second part of an experiment using a bundled database subscription model. Texas A&M University (TAMU) Libraries pursued a multiyear agreement with ProQuest to address "administrative churn." This agreement was known as "ProQuest Comprehensive." During 2014, the final year of the agreement, the TAMU Libraries considered renewal and assessed support for ProQuest Comprehensive. The company is a well-recognized information provider, but to date there are no studies assessing bundled ProQuest content. This article will outline the evaluative criteria developed to assess ProQuest Comprehensive and the steps TAMU Libraries undertook to determine what ProQuest databases to renew, what databases to cancel, and the challenges encountered in the decision-making process.